2012
DOI: 10.5688/ajpe76588
|View full text |Cite
|
Sign up to set email alerts
|

Journal Clubs During Advanced Pharmacy Practice Experiences to Teach Literature-Evaluation Skills

Abstract: Objective. To determine pharmacy students' attitudes and academic performance related to journal club during 2 advanced pharmacy practice experiences (APPEs). Design. Fourth-year pharmacy students were required to complete 3 journal club assignments during drug information and internal medicine APPEs. Assessment. A majority (91.3%) of the 105 students who responded to a 21-item survey instrument indicated that journal club assignments during the drug-information APPE were valuable to their understanding of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…It is likely that most MLE course administrators are aware of MLE activities required in APPEs, since 50% of respondents indicated they precept an APPE, but few appeared to be actively evaluating student APPE performance in MLE-related activities. Mandatory journal clubs during APPE experiences are valuable in development of MLE skills, 19 and evaluation of performance in such clubs could provide MLE course administrators with useful data about student learning in the pre-APPE MLE program. Measuring student APPE performance in MLE activities could also help students identify areas for improvement, which they might otherwise fail to identify; moreover, in their study of pharmacy residents' biostatistics and literature evaluation knowledge, Bookstayer and colleagues found that residents' confidence in their knowledge exceeded their examination performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that most MLE course administrators are aware of MLE activities required in APPEs, since 50% of respondents indicated they precept an APPE, but few appeared to be actively evaluating student APPE performance in MLE-related activities. Mandatory journal clubs during APPE experiences are valuable in development of MLE skills, 19 and evaluation of performance in such clubs could provide MLE course administrators with useful data about student learning in the pre-APPE MLE program. Measuring student APPE performance in MLE activities could also help students identify areas for improvement, which they might otherwise fail to identify; moreover, in their study of pharmacy residents' biostatistics and literature evaluation knowledge, Bookstayer and colleagues found that residents' confidence in their knowledge exceeded their examination performance.…”
Section: Discussionmentioning
confidence: 99%
“…19 Innovations in assessment of student ability to master literature evaluation include repeated testing embedded within and throughout the curriculum, 20 and assessment partway through the APPE year to measure long-term retention of previously-taught material. 21 Distinguishing the standard of practice for MLE instruction and skill-building may give faculty members teaching the subject evidence on which to base curricular design.…”
Section: Introductionmentioning
confidence: 99%
“…It also trains student pharmacists to be able to answer questions during patient care rounds or support an answer with evidence. There are limited published studies about implementation of EBP rotation into advanced pharmacy practice rotations [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…6,[9][10][11] Particularly in Japan where EBM skills are In contrast, in the US school surveyed, where EBM training and presentations are required throughout the didactic courses and experiential education, all environmental barriers were identified by <50% of American students, yet EBM use is still suboptimal. Although several studies showed the effectiveness of EBM training in increasing knowledge in students and practitioners with various methods, including a brief one day workshop, journal club, monograph assignment, and computer-or lecture-based instructions, [29][30][31][32][33][34] knowledge of EBM does not equate to their actual usage of EBM. Some studies have shown no changes in clinician behavior to use EBM even though training improved their knowledge and skills.…”
Section: -24mentioning
confidence: 99%